2019
DOI: 10.17159/2411-9717/17/155/2019
|View full text |Cite
|
Sign up to set email alerts
|

Rock properties and machine parameters evaluation at Rössing Uranium Mine for optimum drill performance

Abstract: This work was carried out to determine the influence of rock properties and drilling machine parameters on the penetration rate at the SJ pit of Rössing Uranium Mine, Namibia. Rock properties (uniaxial compressive strength, tensile strength, and modulus of elasticity) of samples collected were determined in the laboratory. Drilling experiments were conducted in which feed pressure, air pressure, rotary speed, weight on the bit, and torque were varied to measure their effect on the penetration rate. The uniaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Drilling experiments were conducted in which feed pressure, air pressure, rotary speed, weight on the bit, and torque were varied to measure their effect on the penetration rate. The results of the study revealed that penetration rate increases with an increase in the feed pressure [10].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Drilling experiments were conducted in which feed pressure, air pressure, rotary speed, weight on the bit, and torque were varied to measure their effect on the penetration rate. The results of the study revealed that penetration rate increases with an increase in the feed pressure [10].…”
Section: Introductionmentioning
confidence: 89%
“…They demonstrated that there are recommended illumination levels that can improve the mining process and reduce accidents [9]. Adebayo et al (2019) showed that technical parameters of mining machines are very important for mining processes. They investigated the influence of drilling machine parameters on the penetration rate in mines.…”
Section: Introductionmentioning
confidence: 99%
“…The unit is m/min. Under specific working conditions, increasing the feed speed to reduce the construction cost is one of the key decision-making issues for tunnel construction [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unit is m/min. Under specific working conditions, increasing the feed speed to reduce the construction cost is one of the key decision-making issues for tunnel construction [3]. Previous research showed that the feed speed of the jumbo drill is mainly affected by geological conditions and driving parameters.…”
Section: Introductionmentioning
confidence: 99%